2010
DOI: 10.1007/s11605-010-1163-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on Complications and Oncologic Outcomes Following Hepatectomy for Malignancy

Abstract: High BMI patients may have better oncologic outcomes despite higher perioperative morbidity and hepatic complications following hepatectomy. These findings have important clinical and biological implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 32 publications
4
48
0
Order By: Relevance
“…The global obesity epidemic and its relation with cancer [1] has led to an increased awareness of the potential association of obesity with oncologic outcomes after surgery in different types of cancer, with somewhat conflicting findings [21e23]. A recent report on the impact of obesity on posthepatectomy oncologic outcomes found that increasing BMI was related to better overall and recurrence-free survival after liver resection due to malignancy [2]. However, patients with both primary and metastatic liver cancer were included in this study and obesity per se was not significantly associated with survival [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global obesity epidemic and its relation with cancer [1] has led to an increased awareness of the potential association of obesity with oncologic outcomes after surgery in different types of cancer, with somewhat conflicting findings [21e23]. A recent report on the impact of obesity on posthepatectomy oncologic outcomes found that increasing BMI was related to better overall and recurrence-free survival after liver resection due to malignancy [2]. However, patients with both primary and metastatic liver cancer were included in this study and obesity per se was not significantly associated with survival [2].…”
Section: Discussionmentioning
confidence: 99%
“…Data on the impact of obesity on survival after liver resection for CRC metastases are very limited. Although overall survival has been shown to be prolonged with increasing body mass index (BMI) after hepatectomy for various types of cancer [2], this was not confirmed in a recent study in patients undergoing liver resection due to CRC metastases [3]. Finally, diabetes mellitus is frequent in obesity and may have a negative impact on oncologic outcomes in CRC [15], but data on its potential effect on survival after liver resection for CRC metastases are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, few reports have investigated the impact of BMI on surgical outcomes following a hepatectomy for HCC [14][15][16][17]. Moreover, whether cirrhosis and immunity are associated with obesity or lean body mass remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an analysis of the American College of Surgeons National Surgical Quality Improvement Project (ACS NSQIP) dataset demonstrated that severely morbidly obese patients had a higher rate of surgical site infection and wound dehiscence compared to normal weight patients [12]. Additional reports for patients undergoing surgical resection of pancreatic and hepatic malignancies have also shown increased rates of wound infection or intraabdominal abscess in obese patients [14,36]. However, others report that despite the increased technical difficulty, longer operative times, and increase in intraoperative blood loss, obesity does not portend a higher rate of postoperative wound complications [5,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…While long-term obesity-related health concerns such as type 2 diabetes mellitus and cardiovascular disease are wellestablished [3][4][5], recent literature has highlighted the increased risk for the occurrence of certain malignancies, including those arising from the gastrointestinal tract, kidney, breast, and endometrium, among obese adults [6][7][8][9][10]. In addition to increasing reports highlighting the apparent link(s) between chronic obesity and the development of cancer, numerous investigations have reported an increased incidence of documented treatment-related morbidity following the associated surgical and medical management of malignancies among obese adults when compared to individuals with a lean body habitus [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%